Peningkatan Minat Belajar Matematika DenganMenggunakan Media Pembelajaran Berbasis Komputer (Ptk Siswa Kelas Vii Semester Genap Mts NegeriNgemplak Boyolali) - Nurkumalasari, Ika; , Idris Harta, M.A., Ph.D (2016)
Issues that will be examined is the lack of interest of students on learning math. This study aims to increase interest in learning mathematics in class VII MTs Ngemplak for the academic year 2015/2016 with the use of computer-based learning media. This study is classroom action research. The techniques of collecting data are observation, field notes, and documentation. The results showed an increase in interest in learning with a given Action in accordance with the six-step mathematical learning using computer-based learning media, namely: 1. Presentation of information, 2. Questions and responses, 3. Assessment of response, 4. Provision of feeedback responses, 5. Repetition, 6. Segmen lesson setting. This is indicated by an increase in the percentage of each indikator that interest in learning mathematics: a student of the teaching materials before action after action 39,33% increase to 76,67%, extracted students to the teaching materials before action after action incerased 45,33% to 72%, the students' attention during the lesson of prior Action 32,67% after Action increased to 70,67%, the involvement of students to the learning process of a prior act of 40,67% afterthe Action increased to 64%. Based on the description above can be concluded that the application of computer-based learning media can increase student interest.